Clinical Spectrum and Associated Features of Autism Spectrum Disorders: Experience in A Tertiary Level Hospital - Dola, Farah Naz; Kundu, Gopen Kumar (Journal of Bangladesh College of Physicians and Surgeons, 2025)
Background: Autism Spectrum Disorder (ASD) is a neurodevelopmental disorder with a heterogeneous and complex presentation of clinical symptoms related to social communicative and interactive behavior. Thus, the aim was to evaluate the clinical features and associated condition of autism spectrum disorder in Bangladeshi children. Method: A cross-sectional study was done in Out-patient department of Paediatric Neurology, Bangabandhu Sheikh Mujib Medical University, Dhaka from January 2023 to June 2023 Children age 3 to 10 years who satisfied the inclusion and exclusion criteria and met the diagnostic criteria (DSM-V) of ASD were enrolled in this study. In all confirmed cases, clinical features and co-occurring condition were evaluated. Data was collected by a structured questionnaire supplied by department of Pediatric Neurology. Informed written consent was taken from all legal guardians. Results: A total of 75 children of 3-10 years were included. Mean age was 4.27±1.99 with male predominance. Among the associated features; pointing, social interaction, response to call and eye contact were absent in 94.67 %, 97.33%, 92% and 86.67% cases respectively. In this study more than three fourth of studied children were presented with speech delay (80%) and more than half of the children presented with speech regression. ADHD (46.67%), bruxism (25.33%) constipation (22.67%), epilepsy (5.33%), febrile seizure (9.33%) and gratification syndrome (12%) were mostly observed in ASD children. Conclusion: In our study, more than one-third of studied children had ADHD and sleep disturbance followed by bruxism, epilepsy, febrile seizure, gratification syndrome and constipation as other associated features. J Bangladesh Coll Phys Surg 2025; 43: 53-58